Sulfur as a parameter in the suitability assessment of gangue from coal mining for reclamation of opencast excavation, taking into the requirements regarding protection of the soil - Klojzy-Karczmarczyk Beata (E3S Web of Conferences, 2016)
In the process of mining coal considerable amounts of waste material are generated from which it is possible to produce aggregates which could find application in the reclamation of opencast excavations. One of the basic characteristic parameters which may be used to assess the suitability of aggregates for filling reclaimed opencast excavation is sulfur. Total and leachable forms of sulfur content from gangue samples were analyzed in the study. It has been shown that it is possible to select aggregates which are safe for the environment when the main assessment criterion was the percentage of sulfur in the aggregates and sulfate concentration in leaching tests. The research confirmed the role of sulfur as the most important and characteristic parameter which determines where and in what specific conditions the use of gangue or mining waste may be possible. Studies of sulfur content in the samples should be carried out with sufficient periodicity and in a manner enabling to obtain most reliable results which would refer to the entire batch of material. The statistical evaluation makes it possible to estimate to what extent the obtained results of sulfur content in the samples are close to actual values for the entire mass of the material.